Synthesis and Characterization of Gallium Oxide/Tin Oxide Nanostructures via Horizontal Vapor Phase Growth Technique for Potential Power Electronics Application - Lester D. Bernardino; Gil Nonato C. Santos (Advances in Materials Science and Engineering)
The monoclinic β-gallium oxide (Ga2O3) was viewed as a potential candidate for power electronics due to its excellent material properties. However, its undoped form makes it highly resistive. The Ga2O3/SnO2 nanostructures were synthesized effectively via the horizontal vapor phase growth (HVPG) technique without the use of a magnetic field. Different concentrations of Ga2O3 and SnO2 were varied to analyze and describe the surface morphology and elemental composition of the samples using the scanning electron microscopy (SEM) and energy-dispersive X-ray (EDX) spectroscopy, respectively. Meanwhile, the polytype of the Ga2O3 was confirmed through the Fourier transform infrared (FTIR) spectroscopy. The current-voltage (I–V) characteristics were established using a Keithley 2450 source meter. The resistivity was determined using the van der Pauw technique. The mobility and carrier concentration was done through the Hall effect measurements at room temperature using a 0.30-Tesla magnet. It was observed that there was an increase in the size of the nanostructures, and more globules appeared after the concentration of SnO2 was increased. It was proven that the drop in the resistivity of Ga2O3 was due to the presence of SnO2. The data gathered were supported by the Raman peak located at 662 cm−1, attributed to the high conductivity of β-Ga2O3. However, the ε-polytype was verified to appear as a result of adding SnO2. All the samples were considered as n-type semiconductors. High mobility, low power loss, and low specific on-resistance were attained by the highest concentration of SnO2. Hence, it was clinched as the optimal n-type Ga2O3/SnO2 concentration and recommended to be a potential substrate for power electronics application.